2017
DOI: 10.3390/catal7040097
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional TiO2 Structures Incorporated with Tungsten Oxide for Treatment of Toxic Aromatic Volatile Compounds

Abstract: This study assessed 3D WO 3 -TiO 2 nanoflowers (WTNF) synthesized by a combined hydrothermal-ultrasonication-impregnation method for their applicability to the treatment of aromatic volatile compounds under visible-light illumination. The scanning electron microscopy exhibited the formation of 3D structures in the prepared WTNF samples. The X-ray diffraction patterns and energy dispersive X-ray results indicated a successful incorporation of WO 3 into TNF structures. The UV-visible spectroscopy showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Consequently, the enhanced performance of the Ce-doped TiO 2 photocatalyst for the photodecomposition of toluene and o-xylene under the visible-light illumination could also be ascribed to the above-mentioned reaction mechanism. In this study, according to Lee and Jo [41], the reaction mechanism could be modified as follows:Ce-doped TiO 2 + visible light → e − + h + ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the enhanced performance of the Ce-doped TiO 2 photocatalyst for the photodecomposition of toluene and o-xylene under the visible-light illumination could also be ascribed to the above-mentioned reaction mechanism. In this study, according to Lee and Jo [41], the reaction mechanism could be modified as follows:Ce-doped TiO 2 + visible light → e − + h + ,…”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic degradation experiments were conducted using a homemade reactor system similar to that used in our previous work [41], which is displayed in Figure 1. Major component parts of the reactor system included a high purity air cylinder for air supply, a water bath for moisture supply, a thermal chamber for mixing of air and standard substrates, a syringe pump for automatic injection of model toluene and o-xylene gases, gas flowmeters for stream flow rates measurement, a 3-way control valve for sampling gaseous target compounds, and a photoreactor (Pyrex tube with an inner diameter of 3.8 cm and a volume of 133 cm 3 ) with an 8 W conventional daylight lamp (λ = 400–700 nm) or 0.32 W white (λ = 450 nm) or 0.32 W violet (λ = 400 nm) LEDs as a light source.…”
Section: Methodsmentioning
confidence: 99%
“…Different works have also shown a significant improvement in charge transfer between TiO 2 and WO 3 , reaching better photocatalytic performances when the WO 3 concentration is less than 1%. 42,43 It has been demonstrated that higher WO 3 content increases the concentration of recombination centers for electron/hole pairs, contributing to lowering the photoactivity of TiO 2 -WO 3 -based photocatalysts. 44 Kara ´csonyi and co-workers 45 showed that significant differences in the photocatalytic performance of the TiO 2 /WO 3 /(Pt or Au) photocatalysts towards oxalic acid degradation were observed only through the position of the noble metal, if the co-catalyst is deposited on TiO 2 or on WO 3 .…”
Section: Materials Advances Papermentioning
confidence: 99%
“…Doping hybrid WO 3 with other semiconductor to form a heterojunction is well-investigated to be an effective way for improving the separation efficiency of the photo-generated charges or extending the spectral response to full light region [49,50].…”
Section: Heterojunction Constructingmentioning
confidence: 99%